Motivation in Learning English: Do Age and Gender Matter? - Anis Zayyana; Nur Habibah; Astondy Lahamazta; M. Yusuf Baharuddin H. (Edulitics (Education, Literature, and Linguistics) Journal, 2022)
For Indonesians, which are non-native English speakers, learning English is complex due to unpredictable spelling and complicated grammar. Even so, they are able to be experts in English since they possess a key element that is motivation. The learning motivation for each individual is different which may be influenced by gender and age factors. Therefore, this study exists to investigate the distinct motivation possessed by male and female learners as well as different age groups of learners. This study also aims to find out what kind of motivation each group had (intrinsic, instrumental, or integrative motivation) as well as its level. This research was conducted using a cross-sectional study by administering questionnaires to 64 participants. The sample of this study was 2nd, 4th, 6th, and 8th-semester students of English Language Education Department UINSA academic year 2020/2021. The findings revealed that there is a significant difference in motivation to learn English in terms of gender (Sig (2-tailed= .016), but none in distinct age groups (Sig (2-tailed=.707). Besides, both male and female learners obtained a moderate level in instrumental motivation. It was identical to the result of 2nd, 4th, 6th, and 8th-semester students. The findings of this study will be very fruitful for lecturers, students, and other researchers.